Characterization of two new experimental collections in computer and information science containing textual and bibliographic concepts - Fox, Edward Alan 1950- (1983)
Two new collections are described which are particularly useful for investigating the interaction between textual and bibliographic data in the automatic indexing and retrieval of documents. An extension to the vector space model has been proposed whereby various types of concepts are included in the representation of such documents. Experiments using an enhanced version of the SMART system have shown such an extended model to perform better than simpler schemes. The CACM and ISI collections developed for this research should be of value for future related studies